Vitamin D alleviates HFD-induced hepatic fibrosis by inhibiting DNMT1 to affect the TGFβ1/Smad3 pathway - Yueqing Liang; Xueyi Jiang; Xinfeng Zhao; Tiantian Tang; Xiuqin Fan; Rui Wang; Mengyi Yang; Kemin Qi; Yi Zhang; Ping Li (iScience, 2024)
Summary: Increasing evidence points toward vitamin D (VD) having lipometabolism and immune-related properties to protect against related metabolic diseases through influencing DNA methylation with inconsistent results. Simultaneously, its relatively precise molecular metabolism on the progression of metabolic-associated fatty liver disease (MAFLD) remains uncertain. Here, we report an unprecedented role and possible mechanism for VD supplementation on the alleviation of high-fat diet (HFD)-induced MAFLD. Over time, our results demonstrated that metabolic disorders in the HFD-induced MAFLD were aggravated with a certain time-response dependence and accompanied by reduced VD metabolites. All these could be alleviated under sufficient VD supplementation in vivo and vitro. It was partially by inhibiting the expressions of DNMT1 to reverse the epigenetic patterns on the VD metabolism genes and TGFβR1, which ultimately triggered the TGFβ1/Smad3 pathway to result in the development of MAFLD. Furthermore, the protective effects of VD were weakened by the treatment with gene silencing of DNMT1.